CD8+ T‐cell specificity is compromised at a defined MHCI/CD8 affinity threshold. Issue 1 (8th November 2016) - Dockree, Tamsin; Holland, Christopher J; Clement, Mathew; Ladell, Kristin; McLaren, James E; van den Berg, Hugo A; Gostick, Emma; L Miners, Kelly; Llewellyn‐Lacey, Sian; Bridgeman, John S; Man, Stephen; Bailey, Mick; et al.
Abstract : The CD8 co‐receptor engages peptide‐major histocompatibility complex class I (pMHCI) molecules at a largely invariant site distinct from the T‐cell receptor (TCR)‐binding platform and enhances the sensitivity of antigen‐driven activation to promote effective CD8 + T‐cell immunity. A small increase in the strength of the pMHCI/CD8 interaction (~1.5‐fold) can disproportionately amplify this effect, boosting antigen sensitivity by up to two orders of magnitude. However, recognition specificity is lost altogether with more substantial increases in pMHCI/CD8 affinity (~10‐fold). In this study, we used a panel of MHCI mutants with altered CD8‐binding properties to show that TCR‐mediated antigen specificity is delimited by a pMHCI/CD8 affinity threshold. Our findings suggest that CD8 can be engineered within certain biophysical parameters to enhance the therapeutic efficacy of adoptive T‐cell transfer irrespective of antigen specificity.